Distributed Denial of Service Attacks Analysis, Detection, and Mitigation for the Space Control Ground Network: DDoS attacks analysis, detection and mitigation - Shaaban, Ahmed Ramzy; Abdelwanees, Essam; Hussein, Mohamed (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
After launching any satellite, it must be controlled from the ground by the mission control center (MCC) by receiving the health state telemetry and issuing telecommand to control it or to execute its mission so, the network of MCC should be kept safe from any kind of malicious attacks such as Distributed Denial of Service (DDoS). The DDoS attacks could be launched or deployed either by external or internal attackers. DDoS can be defined generally as follow: it is an attempt to exhaust target server resources or consume the available bandwidth to make the target server unavailable to the normal clients. MCC network was simulated using virtual machines – 8 virtual machines. More than 5 types of DDoS tried to attack the simulated MCC network but 2 types were chosen – HTTP and TCP flood- to be designed because of its effectiveness. The analysis was done before and after the attacks by analyzing the captured traffic by Wireshark software. According to the deep analysis results, the detection algorithm was designed to detect the applied attacks. Now the attacker machines are known, so mitigation of theses attacked machines was done by adding blocking rules in the windows firewall automatically. Mitigation was done simply and in a straightforward way but with some instability. Consequently, a new mitigation technique will be developed to block DDoS attacks.